Strategies for promoting autonomous reading motivation: A multiple case study research in primary education - De Naeghel, Jessie; Van Keer, Hilde; Vanderlinde, Ruben (Frontline Learning Research, 2014)
It is important to reveal strategies which foster students’ reading motivation in order to break through the declining trend in reading motivation throughout children’s educational careers. Consequently, the present study advances an underexposed field in reading motivation research by studying and identifying the strategies of teachers excellent in promoting fifth-grade students’ volitional or autonomous reading motivation through multiple case study analysis. Data on these excellent teachers were gathered from multiple sources (interviews with teachers, SEN coordinators, and school leaders; classroom observations; teacher and student questionnaires) and analysed. The results point to the teaching dimensions of autonomy support, structure, and involvement – as indicated by self-determination theory – as well as to reading aloud as critical strategies to promote students’ autonomous reading motivation in the classroom. A school culture supporting students’ and teachers’ interest in reading is also an essential part of reading promotion. The theoretical and practical significance of the study is discussed.